The syntactical government in the Arabic syntax: an analytical study - Yaacob, Solehah@Nik Najah Fadilah (IIUM Press, International Islamic University Malaysia, 2019)
The research focuses on the effectiveness of the syntactical government in interpreting meaning in the Arabic Syntax and in explaining semantic changes resulting from the speakers who deal with phonetic changes in word endings, especially in respect to vowels. It further looks into the factors which contribute to such changes in phonetics and evaluates the significance of the altered meanings in the field of semantics. In order to interpret semantic changes, Classical Arabic which possesses eight cases will determine the changing of the mind transformation process anonymously in comprehending speech utterances. The production of the above process of orientation will affect the precise and accurate meaning construction comprehensively. Thus, the research purpose is to discover the inner structure process before the production of verbal utterances based on issues in Arabic Syntax.